Energy and Momentum Conserving Methods of Arbitrary Order For the Numerical Integration of Equations of Motion. I. Motion of a Single Particle - LaBudde, Robert A.; Greenspan, Donald (University of Wisconsin-Madison Department of Computer Sciences, 1974)
Conventional numerical methods, when applied to the ordinary differential equations of motion of classical mechanics, conserve the total energy and angular momentum only to the order of the truncation error. Since these constants of the motion play a central role in mechanics, it is a great advantage to be able to conserve them exactly. A new numerical method is developed, which is a generalization to arbitrary order of the "discrete mechanics" described in earlier work, and which conserves the energy and angular momentum to all orders. This new method can be applied much like a "corrector" as a modification to conventional numerical approxirnations, such as those obtained via Taylor series, Runge-Kutta, or predictor-corrector formulae. The theory is extended to a system of particles in Part I1 of this work.